Atomic layer-by-layer construction of Pd on nanoporous gold via underpotential deposition and displacement reaction1. Issue 25 (21st March 2015) - Yan, Xuejiao; Xiong, Haiyan; Bai, Qingguo; Frenzel, Jan; Si, Conghui; Chen, Xiaoting; Eggeler, Gunther; Zhang, Zhonghua
<x xml:space="preserve">Abstract</x> Ultrathin Pd films with one to five atomic layers were decorated on nanoporous gold by underpotential deposition and galvanic displacement.